Brazilian Primary Health Care strategies during the COVID-19 pandemic: A scoping review - Bortoli, Maritsa Carla; Sanine, Patricia Rodrigues [UNESP]; Araujo, Bruna Carolina de; Oliveira, Cintia de Freitas; Sanches, Maria Izabel; Tesser, Tais Rodrigues (Abrasco - Brazilian Association Of Collective Health, 2023)
Primary Health Care is the gateway for users to access the Brazilian healthcare sys-tem and has been particularly affected by the COVID-19 pandemic demands. This review systematically identified and mapped evidence regarding novel or adapted strategies developed within PHC during the COVID-19 pandemic in Brazil. Our results are presented as a narrative synthesis following the JBI methodology. They were analyzed and discussed through the lens of the Health Work Process Theory, which al-lowed us to categorize the publications into two principal domains of strategies, managerial and clinical, encompassing strategies that were new, adapted, or maintained in healthcare services. Two hundred twenty-six interventions were iden-tified (130 managerial and 96 clinical) from 49 studies. The new strategies appeared more fre-quently in both domains, while the maintained ones were less prevalent. The array of interven-tions highlights different care models, sometimes aligned with a biomedical approach. In contrast, others focus on comprehensiveness and longitu-dinality based on a person-centered care, in the family, and the community. Thus, this review identified that the same pre-pandemic challenges persist.
Keywords: COVID-19; Primary Health Care; Scoping review. Health Services; Brazil